2022
DOI: 10.1186/s12982-022-00116-9
|View full text |Cite
|
Sign up to set email alerts
|

Candida and the Gram-positive trio: testing the vibe in the ICU patient microbiome using structural equation modelling of literature derived data

Abstract: Background Whether Candida interacts with Gram-positive bacteria, such as Staphylococcus aureus, coagulase negative Staphylococci (CNS) and Enterococci, to enhance their invasive potential from the microbiome of ICU patients remains unclear. Several effective anti-septic, antibiotic, anti-fungal, and non-decontamination based interventions studied for prevention of ventilator associated pneumonia (VAP) and other ICU acquired infections among patients receiving prolonged mechanical ventilation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…2 & 3) and indicate strong contextual effects arising from concurrency which, in any one study, would be inapparent. In the optimal model (model A), these contextual effects are similar in size, but contrary in direction, to the modest direct effect of TAP on Staphylococcus aureus colonization [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…2 & 3) and indicate strong contextual effects arising from concurrency which, in any one study, would be inapparent. In the optimal model (model A), these contextual effects are similar in size, but contrary in direction, to the modest direct effect of TAP on Staphylococcus aureus colonization [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 93%
“…The direct anti-bacterial effect of TAP is more evident within models containing either Pseudomonas or Acinetobacter colonization and infection data than is the case here with the model containing Staphylococcus aureus colonization and infection data. These four modelling studies are based on 328 studies, of which < 200 are common to all three [ 14 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, prolonged use of antibiotics is another cause of candidaemia which may be the main reason why gram-positive bacteria were detected more than gram-negative bacteria in polymicrobial candidaemia episodes. 26 In mixed fungaemia patients, C. albicans and N. glabrata were found to be the most frequent combination in previous studies. [18][19][20][21][22][23] Previous studies have also found that N. glabrata is more frequently isolated in mixed fungaemia infections than in all other candidiasis.…”
Section: Discussionmentioning
confidence: 85%
“…Another reason could be that prolonged hospitalisation is a significant risk factor of candidaemia which also results in the growth of known colonisers. Also, prolonged use of antibiotics is another cause of candidaemia which may be the main reason why gram‐positive bacteria were detected more than gram‐negative bacteria in polymicrobial candidaemia episodes 26 …”
Section: Discussionmentioning
confidence: 99%
“…In these models the antibiotic-BDI are factorized into TAP and PPAP components. The GSEM methodology used here is described in detail in previous publications [19,48].…”
Section: Generalized Structural Equation Modellingmentioning
confidence: 99%